THE ORIGIN OF AFFIXES (Modern education and development, 2025)
This article investigates the etymology and development of English affixes. The paper utilizes both general scientific and specific linguistic methods to analyze word formation, the origins of affixation, and the historical transformation of words. Special emphasis is placed on comparative and structural linguistics to better understand the evolution of affixes in the English language.